Nano-Strategies for Addressing Antimicrobial Resistance Nano-Diagnostics, Nano-Carriers, and Nano-Antimicrobials - Kumar, Vinay; Shriram, Varsha; Shukla, Ravi.; Gosavi, Suresh (Cham : Springer International Publishing : Imprint: Springer, 2022)
Antibiotics, the backbone of modern clinical-medicine, are facing serious challenges from emerging antimicrobial-resistance (AMR), a complicated phenomenon expanding in bacterial species, from nosocomial to community origins, where microbes are no longer sensitive to a range of commonly used antibiotics. AMR has exploded in recent years and is posing a serious threat to human health and survival. This necessitates novel and effective ways of diagnosis, drug-delivery, and treatment; nanotechnology and advanced nanomaterials are hailed as a potent solution in containing AMR. The main thrust of this volume is to explain the most current research on the central theme of potential use of nano-approaches for diagnosis, detection, drug-delivery and as antimicrobial agents against drug-resistant pathogenic microbes. This book provides an integrated blend of basic and advanced information for students, scholars, scientists and practitioners, interested or already engaged in research in these areas. We have brought together leading international authors to present and highlight various aspects of nanotechnology in combating AMR in WHO-prioritized microbes. Topics range from advances in nanomaterial synthesis, characterization, functionalization and improvisation, as well as applications in sensing, diagnosis of AMR, and their therapeutic and drug-delivery potential against MDR and XDR microbial phenotypes.
1.The History of Antibiotics Illumes the Future of Antimicrobial Peptides Administered Through Nano-Systems -- 2.Current approaches and prospects of nanomaterials in rapid diagnosis of antimicrobial resistance -- 3.Nanomaterials-mediated delivery of antimicrobial agents 'The Nanocarriers' -- 4.Nanoparticle functionalization: Approaches and applications -- 5.Nano-adjuvants as effective next-generation antimicrobial agents -- 6.Limiting antibiotic-resistant bacteria using multifunctional nanomaterials -- 7.Microbial resistance mechanisms and potential of metal-organic framework in mitigation thereof -- 8.Silver-based Nano-Formulations for Treating Antibiotic-Resistant Microbial Strains -- 9.Gold Nanoparticles: A Lethal Nanoweapon against Multidrug Resistant Bacteria -- 10.Antimicrobial Potentials of Zinc and Iron Oxide Nanoparticles -- 11.Carbon Nanostructures for Fighting Antimicrobial Resistant Bacteria -- 12.Nano-formulations against Multidrug Resistant Members of ESKAPE pathogens.
Keywords: Plant biotechnology; Nanotechnology; Biotechnology; Medical microbiology; Plant Biotechnology; Nanotechnology; Biotechnology; Medical Microbiology